SNAPPIX: Efficient-Coding-Inspired In-Sensor Compression for Edge Vision - Lin, Weikai; Ma, Tianrui; Boloor, Adith; Feng, Yu; Xing, Ruofan; Zhang, Xuan; Zhu, Yuhao (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Energy-efficient image acquisition on the edge is crucial for enabling remote sensing applications where the sensor node has weak compute capabilities and must transmit data to a remote server/cloud for processing. To reduce the edge energy consumption, this paper proposes a sensor-algorithm co-designed system called SNAPPIX, which compresses raw pixels in the analog domain inside the sensor. We use coded exposure (CE) as the in-sensor compression strategy as it offers the flexibility to sample, i.e., selectively expose pixels, both spatially and temporally. SnapPix has three contributions. First, we propose a task-agnostic strategy to learn the sampling/exposure pattern based on the classic theory of efficient coding. Second, we codesign the downstream vision model with the exposure pattern to address the pixel-level non-uniformity unique to CE-compressed images. Finally, we propose lightweight augmentations to the image sensor hardware to support our in-sensor CE compression. Evaluating on action recognition and video reconstruction, SnapPix outperforms state-of-the-art video-based methods at the same speed while reducing the energy by up to 15.4 ×. We have open-sourced the code at: https://github.com/horizonresearch/SnapPix.